Conscious engagement in undergraduate male nursing students: facilitating voice through an action research project - Maykut, Colleen; Lee, Andrew; Argueta, Nelson Garcia; Grant, Sean; Miller, Cole (My University, 2016)
Although women have made significant progress into traditionally male-dominated professions, such as medicine and engineering, the same cannot be said of men in the nursing profession. Utilizing a critical social theory perspective, an action research project was designed to encourage participants, current male nursing students and alumni of MacEwan University, to share their educational experiences through narratives. The significance of this action research project is threefold: (1) to understand the phenomena of the MacEwan male nursing student, (2) to develop strategies and coping mechanisms to address concerns voiced by participants’ experiences, and (3) to create evaluative tools to assess effectiveness of such strategies.
Keywords: male nurses; post-secondary education